2012
DOI: 10.1002/adma.201103958
|View full text |Cite
|
Sign up to set email alerts
|

Patchiness of Embedded Particles and Film Stiffness Control Through Concentration of Gold Nanoparticles

Abstract: Patchy particles are fabricated using a method of embedding-into and extracting-from thick, biocompatible, gel-like HA/PLL films. Control over the patchiness is achieved by adjusting the stiffness of films, which affects embedding and masking of particles. The stiffness is adjusted by the concentration of gold nanoparticles adsorbed onto the surface of the films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…Detailed analysis of the liposome position within the film has shown that they immerse by about half of their size when they come in contact with the surface of the film. This behavior is similar to the behavior of latex particles or polymer microcapsules being in contact with the HA/PLL multilayers [78,79]. Full immersion of vesicles (about 100 nm in diameter) within the film can be achieved just by a few additional LbL coating steps with the same polymers.…”
Section: Loading With Nanocontainerssupporting
confidence: 64%
See 1 more Smart Citation
“…Detailed analysis of the liposome position within the film has shown that they immerse by about half of their size when they come in contact with the surface of the film. This behavior is similar to the behavior of latex particles or polymer microcapsules being in contact with the HA/PLL multilayers [78,79]. Full immersion of vesicles (about 100 nm in diameter) within the film can be achieved just by a few additional LbL coating steps with the same polymers.…”
Section: Loading With Nanocontainerssupporting
confidence: 64%
“…Reservoir properties of the HA/PLL film allow the embedding of small and rather large objects, also large carriers such as microcapsules [25,74,78,79,97]. Light-sensitive multilayer microcapsules modified with gold nanoparticles have been embedded into the HA/PLL film by spontaneous loading [25].…”
Section: Light-triggered Deliverymentioning
confidence: 99%
“…Furthermore, multi-compartment particles/capsules are predicted to be of potential use in theranostic applications where one carrier would perform a dual function: diagnostic and therapeutic [128,129]. Direct synthesis of anisotropic particles can be another approach to anisotropic carriers [130], while controlled patchiness [131] provides another advanced functionality. In addition to particles described above, some exotic templates include also bacteria [132], microcrystals [133], and worms [134].…”
Section: Anisotropic Capsules and Anisotropic Carriersmentioning
confidence: 99%
“…Films with higher stiffness are produced by increasing the concentration of gold nanoparticles on their surface. In fact, the E-modulus of such films was observed to increase from less than 300 MPa to more than 900 MPa (over three fold increase) by addition of 900 µl of gold nanoparticle solution [10]. On the other hand, this increased stiffness of films can be used for controlling protrusion of embedded particles.…”
mentioning
confidence: 98%
“…And if the nanoparticles alter the stiffness of the films, then it is expected that particles or capsules adsorbed to their surface would protrude differently depending on the concentration of nanoparticles. Such an approach represents a facile method to control the patchiness of particles in a completely biocompatible process [10]. Alternatively, mechanical properties control of films can be achieved by polyanions mixture [11], while their modification can be performed with microcapsules [12].…”
mentioning
confidence: 99%